Management of hepatorenal syndrome and associated outcomes: a systematic review - Anahid Hamidianjahromi; Jamshid Roozbeh; Shahrokh Ezzatzadegan Jahromi; Mohamad Hossein Rezazadeh; Leila Malekmakan (BMJ Open Gastroenterology)
Background Hepatorenal syndrome (HRS), a multiorgan condition of acute kidney injury, is seen in advanced liver disease. This study aims to evaluate the current treatment for HRS.Methods The authors searched PubMed, Scopus and Google Scholar literature. After quality assessment, 31 studies were included in this review. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology and the population, intervention, comparison and outcome scheme were used. We included human-controlled trials that evaluate the current treatment for HRS. Two authors independently screened articles for inclusion, extracted data and assessed the quality of included studies.Results This study investigated the studies conducted on the effects of different treatments on follow-up of HRS patients. We gathered 440 articles, so 31 articles remained in our study. Of which 24 articles were conducted on terlipressin versus placebo or other treatments (midodrine/octreotide, norepinephrine, etc) that showed the higher rate of HRS reversal was detected for terlipressin in 17 studies (10 of them were significant), 2 studies achieved an insignificant lower rate of the model for end-stage liver disease score for terlipressin, 15 studies showed a decreased mortality rate in the terlipressin group (4 of them were significant).Conclusion This review showed that terlipressin has a significantly higher reversal rate of HRS than the other treatments. Even the results showed that terlipressin is more efficient than midodrine/octreotide and norepinephrine as a previous medication, in reverse HRS, increasing patient survival.